Evaluation of Orthodontic Treatment Time Using Peer Assessment Rating Index - Saad S Gasgoos (University of Mosul, College of Dentistry, 2011)
Aims of the study: To assess the effect of age, sex, Angle classification, extraction of the teeth and severity of malocclusion on orthodontic treatment duration using Peer Assessment Rating (PAR) index. Materials and Methods: Upper and lower study models of 100 patients (50 males and 50 females) before and after orthodontic treatment with age ranged between 15-25 years old of different types of malocclusion were selected from four private orthodontic clinics in Mosul City according a certain criteria. The data were collected for each patient from their case sheet includes age, gender, PAR index before and after treatment, treatment time in months, extraction cases and the Angle classification of malocclusion. The PAR index was measured according to criteria of Richmond et al, and then Pearson Correlation Coefficient was used among these variables. Results: The percentage of reduction in PAR index was highest in Class I malocclusion (97.2%) followed by Class II (92.2%) and Class III (90%). No significant correlation was observed between the percentage of reduction of PAR index and time of treatment, also no significant correlation was found between patient age and treatment time at this age group (15-25 years), but there was a significant correlation between PAR index before treatment and the treatment time in Class I non extraction, Class II and Class III malocclusion extraction cases. The mean treatment time was 14.44 months for Class I, 16.92 months for Class II, 21.25 months for Class III malocclusion. Conclusions: both treatment duration and cost effectiveness could be clear for patient before starting the treatment when using the PAR index to evaluate the malocclusion severity